Biogeomorphology of the Mediterranean Posidonia oceanica seagrass meadows. Issue 1 (6th April 2016) - Vacchi, Matteo; De Falco, Giovanni; Simeone, Simone; Montefalcone, Monica; Morri, Carla; Ferrari, Marco; Bianchi, Carlo Nike
Abstract: Here we review the multiple interactions between the endemic Mediterranean seagrass, Posidonia oceanica, and coastal geomorphologic processes as an outstanding example of biogeomorphology, taking into account recent advances in the field. Seagrass meadows are among the most important elements for the functioning of marine coastal ecosystems, and represent a major focus for research and conservation. Being considered a priority habitat, P. oceanica meadows are protected by several European Union directives and national laws. In this paper we examine: the role of sedimentary features in controlling the development of the meadows; the interplay between P. oceanica leaf litter (i.e. beached necromass) cast ashore and erosional‐depositional processes on the beaches; the interactions between meadows and nearshore hydrodynamics, and; possible linkages between geomorphological features of the seafloor and the architecture of meadows. Finally, we provide perspectives for future research on P. oceanica and other Mediterranean seagrass meadows in a biogeomorphological context with specific reference to climate change. Copyright © 2016 John Wiley & Sons, Ltd.